RESPONSE OF POTATO TO POTASSIUM FERTILIZER SOURCES AND APPLICATION METHODS IN ANDISOLS OF WEST JAVA - Gunadi, Nikardi (Indonesian Journal of Agricultural Science, 2009)
An experiment to determine the response of potato to potassium(K) fertilizer sources and application methods in Andisolsof West Java was conducted at a farmerâs field in the highlandarea of Pangalengan (1400 m asl.), West Java from August toNovember 2004. The treatments consisted of two K fertilizersources (potassium chloride-KCl and potassium sulphate-K2SO4),two K rates (150 and 250 kg K2O ha-1), and three applicationmethods (single, split, and split combined with foliar application),were arranged in a randomized complete block design withfour replications. In the single application treatment, K wasapplied at planting, while in the split application treatment theK was applied half rate at planting and the rest at 6 weeks afterplanting (WAP). In the split combined with foliar applicationtreatment, the K fertilizer was applied half rate at planting, aquarter rate at 6 WAP and another quarter rate by foliar sprayingat 7, 8 and 9 WAP. The results showed that plant height was notsignificantly affected by the treatment (P >0.05). However, thesources and application methods of K fertilizer affected canopycover, crop cover weeks (CCW), tuber dry weight (DW), andtotal plant DW at 10 WAP. Potatoes supplied with K2SO4 eitherin split or split combined with foliar application had significantlyhigher percent canopy cover, CCW, tuber DW, and totalplant DW than those supplied with K fertilizer in single application.Potatoes supplied with K2SO4 had a higher tuber yieldcompared to those fertilized with KCl, especially under split orsplit combined with foliar application. To attain the same levelof tuber yield as in the split combined with foliar applicationmethod, the rate of K2SO4 should be increased from 150 to 250 kgK2O ha-1 when using single application. It is therefore suggestedthat K2SO4 for potatoes should be used in split applicationcombined with foliar application.